스켈링 건강보험 서비스에 대한 인식 및 만족도 - 정재연; Jae Yeon Jung; 임미희; Mi Hee Lim (Han'guk Ch'iwisaeng Hakhoe chi, 2015)
Objectives: The purpose of this study was to examine awareness and satisfaction toward health insurance coverage of scaling. Methods: A self-reported questionnaire was completed by 221 patients receiving scaling service from July to August, 2014. The informed consent was approved after the explanation of purpose of the study. The questionnaire consisted of general characteristics of the subjects, awareness toward health insurance coverage of scaling, scaling service covered by health insurance, and satisfaction with health insurance service. Results: Those recognizing the health insurance service extension accounted for 87.3 percent and 67.4 percent answered that the appropriate coverage age would be 20 years old. The recommendable frequency of scaling was once a year and this accounted for 49.3 percent. Fifty percent of the subjects thought health insurance coverage of scaling would be reasonable and 34.8 percent acquired the information from mass media. The most common service providers were dental hygienists and the length of service was from 20 to 30 minutes. The contents of service included scaling service, toothbrushing method, and oral care. The satisfaction was 4.39 points. Conclusions: The health insurance coverage of scaling will improve the oral health and quality of life in Korean adults. So the government should try to extend the scaling coverage by health insurance and the frequency of scaling.